PENGETAHUAN TENTANG COVID-19 (COVID LITERACY) DI KALANGAN MASYARAKAT INDONESIA DI MASA PANDEMI LANJUT - Rouli Manalu; Tandiyo Pradekso; Djoko Setyabudi (Universitas Katolik Soegijapranata, 2022)
This research aims to elaborate the knowledge of people regarding Covid-19 and the characteristics of the Corona Virus in the later stage of the pandemic. The latest pandemic that had happened prior to pandemic Covid-19 with arguably similar scale was the Spanish Flu that happened in 1918, when the network of global connection still sparsely established. On the contrary, pandemic Covid-19 happened in globalized network society and in the era when information can be access easily and can be spread rapidly and massively. The overwhelming amount of information about Covid-19, both accurate and inaccurate information had flooded the public sphere and public conversation, event WHO coined the situation as “infodemic”. However, whether the vast amount of information has generated a well-informed public is need to be scrutinized further. Using the Covid-19 literacy scale develop by Naveed, et.al., in 20202, which consist of two dimensions; infection spread and symptoms; and infection prevention and treatment, this research investigates the knowledge or the literacy of Covid among adults in Indonesia. The result shows that the vast amout information can shape the knowledge of the respondent to be literate of the Covid-19. It indicates that respondents were able to take and retain accurate information regarding Covid-19. This research, however, does not say that inaccurate and false information would not cause harmful effect. The literacy endeavor must continue to be pursued to build literate society.